Physical condition preparation of combat sport athletes for fighting simulation in experimental research: coach perspective analysis - Trisnar Adi Prabowo (Pedagogy of Health, 2025)
Background and Study Aim. There is a lack of scientific information on how much time is ideal for physical conditioning preparation needed before conducting experimental research in the form of a pretest. The purpose of this study is to fill the information gap by collecting data and in-depth analysis of the preparation time considered optimal by coaches in facing match simulations at pretest time.